Implementation Of The Sale And Purchase Agreement And The Status Of Ownership Of Land Rights At Apartment In Payon Amartha View Of Semarang - Riska Fauziana; Rizal Anugrah Bachriar; Anis Mashdurohatun (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2019)
The study entitled